Creating a Class Plan to Strengthen Marital Relationships During Pregnancy in Japan (International Journal of Studies in Nursing, 2024)
Background Child-rearing support programs in Japan have focused on supporting families (especially mothers) after their children are born. Maternal and child healthcare services during pregnancy mainly target mothers and their children. Although programs for fathers (such as parent–teacher classes) are gradually being implemented, support for fathers will become more important in the future. Objectives We reviewed studies conducted in Japan on support for fathers during pregnancy (especially those focusing on the content of classes) and examined the content and methods of classroom approaches for fathers. Then, the content of the exercises related to the Becoming Parents Program was examined. The BPP, which was developed in Washington D.C., is an experiential program that focuses on strengthening the couple’s partnership, particularly in the transition to fatherhood. Focusing on the father–partner relationship itself, this study aimed to examine the kind of support methods and content would be best for planning a class during pregnancy in Japan and developing a class plan. Methods We searched the nursing literature for studies on classes or classes for expectant fathers that included educational content on fathers during pregnancy. Thirteen domestic studies were included in the literature review. Next, 16 exercises from the BPP book were analyzed for content. Results Expectant fathers sought specific information on support for their spouses. The 16 exercises in the BPP book entitled “The Speaker-Listener Technique and Problem Solving” were found to be fundamental skills. A proposed class for expectant parents incorporating the basics of BPP was designed. Conclusions Although there are differences in social backgrounds, cultures, and family backgrounds between Japan and other countries, we believe that the basic skills can be commonly used. In Japan, it is necessary to consider holding classes for parents to strengthen their marital relationship during pregnancy. This work was supported by JSPS KAKENHI Grant Number JP20K11127